Engineered isoprene production from Chlamydomonas reinhardtii using herbicide selection markers and CO2-fed cultivation optimization through multi-parallel photobioreactor headspace gas analysis - Razan Z. Yahya; Sebastian Overmans; Gordon B. Wellman; Kyle J. Lauersen (Algal Research, 2025)

The trade-offs associated with the adaptions of marine microalgae to high CO2 and warming - Xiao Liang; John A. Raven; John Beardall; Sebastian Overmans; Jianrong Xia; Peng Jin (Marine Environmental Research, 2025)

Interactions between ocean acidification and multiple environmental drivers on the biochemical traits of marine primary producers: A meta-analysis - Baoyi Peng; Jingyao Li; Hao Zhang; Sebastian Overmans; Yipeng Wang; Leyao Xu; Yuan Jia; Bin Huang; Fangzhou Liu; Peixuan Liu; Mengting Xiao; Mengcheng Ye; et al. (Marine Environmental Research, 2024)

Multi-trait analysis reveals large interspecific differences for phytoplankton in response to thermal change - Mengcheng Ye; Mengting Xiao; Shufei Zhang; Jiali Huang; Jiamin Lin; Yucong Lu; Shiman Liang; Jingyuan Zhao; Xiaoying Dai; Leyao Xu; Mingke Li; Yunyue Zhou; et al. (Marine Environmental Research, 2023)

Differential susceptibility of Red Sea Pocilloporidae corals to UVB highlights photoacclimation potential - Sebastian Overmans; Susana Agustí (Frontiers in Marine Science, 2023)
Despite being exposed to extreme water temperatures and solar irradiances, Red Sea corals are relatively resistant to bleaching. While their thermal tolerance is well described, little is known about their resistance to ultraviolet-B radiation (UVB). Here, we performed a short-term (2 days) UVB-removal incubation with Stylophora pistillata , and in situ measurements with Pocillopora verrucosa complemented by a long-term (46 days) transplantation and UVB-removal experiment. Using a suite of physiological parameters (effective quantum yield ( F v ’/ F m ’), oxidative stress (lipid peroxidation, LPO), and primary production), we assessed the impacts of UVB on the physiology and acclimation capacity of Red Sea corals. Shielding S. pistillata from UVB did not change the gross primary production or F v ’/ F m ’, and respiration and LPO in the host remained unaffected. In situ, P. verrucosa exhibited less varying and significantly higher F v ’/ F m ’ in 8 m depth (0.61 ± 0.04) than in 4 m (0.52 ± 0.06), 2 m (0.51 ± 0.09), and 0.5 m (0.50 ± 0.11), where water temperatures ranged from 30.5–33.4, 30.6–34.0, 30.8–34.5, 30.6–37.3°C and daily UVB exposures averaged 0.9, 2.9, 11.8 and 21.4 kJ m -2 , respectively. F v ’/ F m ’ correlated the strongest with UVB (-0.57), followed by PAR (-0.54) and temperature (-0.40), suggesting that UVB is a key determinant of photosynthetic efficiency. F v ’/ F m ’ of upward transplanted specimens (T 1m) was initially decreased but gradually increased and reached the same values as shallow corals (1 m) after 44 days. UVB removal significantly increased the F v ’/ F m ’ of transplanted corals in the first 20 days. Oxidative stress was initially highest in T 1m samples under full sunlight but equalized with 1 m specimens by day 46, whereas oxidative stress was significantly reduced by day 4 in T 1m corals sheltered from UVB. Overall, UVB-removal generally had little impact on the physiology of shallow-water S. pistillata and P. verrucosa but considerably accelerated the acclimation of upward transplanted corals. Our study highlights that UVB is a crucial stressor governing the photoacclimation capacity of these Red Sea coral species.

Biomass generation and heterologous isoprenoid milking from engineered microalgae grown in anaerobic membrane bioreactor effluent - Bárbara Bastos de Freitas; Sebastian Overmans; Julie Sanchez Medina; Pei-Ying Hong; Kyle J. Lauersen (Water Research, 2023)

The Combined Effects of Ocean Acidification and Heavy Metals on Marine Organisms: A Meta-Analysis - Peng Jin; Jiale Zhang; Jiaofeng Wan; Sebastian Overmans; Guang Gao; Mengcheng Ye; Xiaoying Dai; Jingyuan Zhao; Mengting Xiao; Jianrong Xia (Frontiers in Marine Science, 2021)
Ocean acidification (OA) may interact with anthropogenic pollutants, such as heavy metals (HM), to represent a threat to marine organisms and ecosystems. Here, we perform a quantitative meta-analysis to examine the combined effects of OA and heavy metals on marine organisms. The results reveal predominantly additive interactions (67%), with a considerable proportion of synergistic interactions (25%) and a few antagonistic interactions (8%). The overall adverse effects of heavy metals on marine organisms were alleviated by OA, leading to a neutral impact of heavy metals in combination with OA. However, different taxonomic groups showed large variabilities in their responses, with microalgae being the most sensitive when exposed to heavy metals and OA, and having the highest proportion of antagonistic interactions. Furthermore, the variations in interaction type frequencies are related to climate regions and heavy metal properties, with antagonistic interactions accounting for the highest proportion in temperate regions (28%) and when exposed to Zn (52%). Our study provides a comprehensive insight into the interactive effects of OA and HM on marine organisms, and highlights the importance of further investigating the responses of different marine taxonomic groups from various geographic locations to the combined stress of OA and HM.

Giant clams in shallow reefs: UV-resistance mechanisms of Tridacninae in the Red Sea - Susann Rossbach; Sebastian Overmans; Altynay Kaidarova; Jürgen Kosel; Susana Agustí; Carlos M. Duarte (Coral Reefs, 2020)

Unraveling the Seasonality of UV Exposure in Reef Waters of a Rapidly Warming (Sub-)tropical Sea - Sebastian Overmans; Susana Agustí (Frontiers in Marine Science, 2020)

Increasing temperature within thermal limits compensates negative ultraviolet‐B radiation effects in terrestrial and aquatic organisms - Peng Jin; Sebastian Overmans; Carlos M. Duarte; Susana Agustí (Global Ecology and Biogeography, 2019)
Aim The interactive effects of increased temperature and ultraviolet‐B (UV‐B) radiation on terrestrial and aquatic biota remain poorly understood. Our goal is to increase knowledge by providing a comprehensive assessment of the combined effects of warming and increased UV‐B on organisms across these domains. Location Global. Time period 1995–2016. Major taxa studied Terrestrial plants and animals, and marine and freshwater microalgae, macroalgae and animals. Methods We examined, using a meta‐analysis based on 1,139 published experimental assessments, the combined effects of temperature and UV‐B across terrestrial, freshwater and marine biota. We characterized the prevailing mode of combined effects (additive, synergistic or antagonistic), and assessed whether these were dose‐dependent or differed between terrestrial, freshwater and marine species, or between organisms growing in the Northern and Southern Hemispheres. Results Our results show that the two stressors generally acted opposingly, with a significant positive effect of increased temperature and a significant adverse effect of elevated UV‐B radiation. Regarding their interactive impact, additive interactions (84%) appeared to be much more common compared with multiplicative (16%) effects. The frequencies of interaction types differed significantly among the three habitats and different plant functional groups. The proportion of both synergistic and antagonistic effects increased with increasing magnitude of temperature and UV‐B changes, suggesting that additivity is constrained by an organism's thermal and physiological limits. Main conclusions Our analysis demonstrates that due to their mostly opposing nature, elevated temperature, within the thermal limits of organisms, tends to compensate for the negative impact of UV‐B radiation when acting together, while their additive interaction is likely to assist impact prognosis. Our study, therefore, provides new insights into the predictions of the interactive effects of global change drivers across different habitats.